OBESITAS - Yusti Siana; Prima Adelin; Mhd Nurhuda; Dian Puspita; Verindra Anggraini (Yayasan Nusantara Hasana Berdikari, 2026)
Obesity is a complex condition characterized by excessive accumulation of body fat and is associated with various metabolic disorders and chronic diseases. Its causes are multifactorial, involving genetic, metabolic, behavioral, and environmental factors. An imbalance between energy intake and energy expenditure is the primary contributor to obesity development. Pathophysiologically, obesity involves hormonal dysregulation, such as leptin resistance, and insulin resistance that triggers disturbances in glucose and lipid metabolism. The diagnosis of obesity is generally based on Body Mass Index (BMI) measurement, while its management includes lifestyle modification, pharmacological interventions, and bariatric surgery for severe cases. Obesity is closely linked to increased risks of cardiovascular, metabolic, hepatobiliary, respiratory, musculoskeletal, and psychological complications. Prevention requires promotive and preventive strategies, including public education, early detection, and community-based interventions. A comprehensive approach is essential to reduce the public health burden caused by obesity.